Comparative Personality Traits Assessment of Three Species of Communally Housed Captive Penguins - Giovanni Quintavalle Pastorino; Richard Preziosi; Massimo Faustini; Giulio Curone; Mariangela Albertini; Dawn Nicoll; Lorna Moffat; Romain Pizzi; Silvia Mazzola (Animals, 2019)
Understanding animal personalities has notable implications in the ecology and evolution of animal behavior, but personality studies can also be useful in optimizing animal management, with the aim of improving health and well-being, and optimizing reproductive success, a fundamental factor in the species threatened with extinction. Modern zoos are increasingly being structured with enclosures that host different species, which permanently share spaces. This condition has undeniable positive aspects, but, in some species, it could determine the appearance of collective or synchronized behaviors. The aim of this study was to verify, in a colony of three species of communally housed penguins (Pygoscelis papua, Aptenodytes patagonicus and Eudyptes moseleyi), through a trait-rating assessment, if interspecific group life impacts on the expression of personality traits, and if it is possible to highlight specie-specific expression of personality traits, despite the influence of forced cohabitation. For many of the personality traits we analyzed, we have observed that it was possible to detect an expression that differed, according to the species. From a practical point of view, these data could ameliorate the management of the animals, allowing to design animal life routines, according to the different behavioral characteristics of the cohabiting species.